2016
DOI: 10.1186/s13048-016-0292-1
|View full text |Cite
|
Sign up to set email alerts
|

EphA5 protein, a potential marker for distinguishing histological grade and prognosis in ovarian serous carcinoma

Abstract: BackgroundOvarian serous carcinoma (OSC) is the most common ovarian epithelial malignancy. Disregulation of Eph/ephrin signaling has been implicated in oncogenesis and tumor progression. EphA5 receptor is one of large families of Eph tyrosine kinase receptor and is documented in the development of nervous system. Till now, there is no published data about the role of EphA5 in ovarian epithelial neoplasmas.MethodsThis study aims to investigate the expression of EphA5 protein in ovarian serous carcinoma, and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
2
20
1
Order By: Relevance
“…EphA5 was negatively expressed in 30/110 (27.3%) and positively expressed in 80/110 (72.3%) samples from patients with gastric cancer. Although the specificity of the anti-EphA5 antibody was confirmed in an ovarian cancer study (21), the absence of a positive control is a limitation of the present study. EphA5 protein expression was reduced in the majority of gastric cancer tissue samples, compared with non-tumor gastric epithelia.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…EphA5 was negatively expressed in 30/110 (27.3%) and positively expressed in 80/110 (72.3%) samples from patients with gastric cancer. Although the specificity of the anti-EphA5 antibody was confirmed in an ovarian cancer study (21), the absence of a positive control is a limitation of the present study. EphA5 protein expression was reduced in the majority of gastric cancer tissue samples, compared with non-tumor gastric epithelia.…”
Section: Discussionmentioning
confidence: 79%
“…In a previous study, it was determined that EphA5 was expressed in the normal fallopian tube (100%), benign epithelial ovarian tumor cases (100%) and the majority of ovarian serous borderline tumor cases (76%) (5). Reduction of EphA5 expression was observed in ovarian serous carcinoma cases (31%) and was associated with tumor grade and International Federation of Gynecology and Obstetrics stage (21). In the present study, immunohistochemistry (IHC) was performed to evaluate EphA5 protein expression in a set of specimens from patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that EPHA5 is abnormally expressed in many tumors, such as prostate, ovarian, renal cell, colorectal, and breast cancer, and is inversely correlated with patient prognosis (17, 28). However, there is very little research regarding the role of EPHA5 in the prognosis of patients with HER2‐positive breast cancer who received trastuzumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…According to the performance of HUVECs overexpressing the above two candidate TFs and change in the mRNA levels of candidate genes, we assumed that SPDEF could act through EPHA5, ZBTB46, or SASH1 to act as a suppressor in HUVECs, while SOX4 has a promoting effect through regulating MMP12 and HIVEP3. Decreased EPHA5 level is associated with poorer tumor prognosis [35,36], and SASH1 acts as a tumor suppressor [37]. ZBTB46 likely has an inhibitory role in angiogenesis [38].…”
Section: Discussionmentioning
confidence: 99%